Measurement of plasma 5-hydroxyindoleacetic acid as a possible clinical surrogate marker for the action of antivascular agents. - Kestell, P; Zhao, L; Jameson, M; Stratford, MR; Folkes, L; Baguley, B (2001)
BACKGROUND: Serotonin (5HT), a naturally occurring vasoactive substance, is released from platelets into plasma under various pathological conditions. Recently, anticancer drugs that act by selectively disrupting tumour blood flow have been found to increase plasma 5HT concentrations in mice. Two such antivascular agents, flavone acetic acid (FAA) and 5,6-dimethylxanthenone-4-acetic acid (DMXAA), have completed Phase I clinical trial and raise the important question of whether suitable surrogate markers for antivascular effects can be identified. METHODS: 5HT is unstable to storage, precluding routine clinical assay, but the 5HT metabolite, 5-hydroxyindoleacetic acid (5HIAA) accumulates in plasma following 5HT release and is a more suitable marker because of its greater stability. We have developed an automated procedure for the assay of the low concentrations of 5HIAA found in humans by combining solid-phase extraction with high-performance liquid chromatography (HPLC). RESULTS: Efficient separation of 5HIAA from possible interfering substances in human plasma, including a variety of pharmaceutical agents, was achieved on C18 columns using cetyltrimethylammonium bromide (CETAB) as an organic modifier. Adequate precision, accuracy and sensitivity were achieved by electrochemical detection (ECD) at +400 mV. Analysis of plasma from two patients treated with DMXAA in a Phase I trial demonstrated DMXAA-induced elevation of plasma 5HIAA with a time course similar to that previously described in mice. CONCLUSIONS: Measurement of changes in plasma 5HIAA provides a new approach to the monitoring of therapies with an antivascular effect. The assay is sensitive to dietary sources of 5HT, which should be minimised.